Rod breakage due to complete resorption of bone graft in a patient with occipito-cervial fusion - Thapa, Pramesh; Paudel, Sushil; Adhikari, Shirish; Lakhey, Rajesh Bahadur; Pokharel, Rohit Kumar (Nepal Orthopaedic Association Journal, 2020)
Implant failure after occipitocervical fusion (OCF) is rare. A 47 year old male presented with neck pain and features of cervical myelopathy. Imaging of cervical spine showed instability at C2/C3 and compressive myelopathy due to tubercular infection. He underwent OCF with bone graft. Post operatively he improved clinically. After 7 months of initial operation, there was reemergence of symptoms suggesting rod breakage. Revision operation was planned. Per operative finding was complete resorption of the bone graft. At 2 months follow-up, the hardware and bone graft was found to be in good position with significant improvement in symptoms. We concluded that complete resorption of bone graft from first surgery led to poor post-operative fusion and rod breakage.